Potential intervention targets to promote physical activity among people with multiple sclerosis: A scoping review protocol for evidence of moderation - Emily R. Jakob; Steve Amireault; Jason B. Reed; Shih-Chun Kao; Robert W. Motl; Elizabeth A. Richards; Reese C. Kerschner (PLoS ONE, 2026)
Introduction Although currently available behavioral interventions can be effective at promoting physical activity among people with multiple sclerosis (MS), there is inconsistency in the magnitude of reported intervention effects. This highlights the importance of exploring the available evidence of moderation, which can help inform decisions about whether a specific set of behavior change techniques and strategies should be adopted for different contexts or segments of the population. Therefore, we propose a scoping review protocol to guide a summary of the body of work that has attempted to understand, explain, predict, or change physical activity behavior (context) among people with MS (population), with an eye on evidence of moderation (concept). Methods and analyses Studies that report on a sample of people with MS in the context of physical activity will be included for review. The search strategy includes the combing of eight electronic databases, a hand search of the reference lists for all included studies and relevant knowledge syntheses, and a citing reference search for all included studies using Web of Science. Two reviewers will single-screen titles and abstracts and independently assess each study based on a full text review. Types of multiple sclerosis populations included, and types of research methodologies used in the studies will be presented using a waffle chart. Results pertaining to the evidence of moderation will be presented using a tree graph. Dissemination Results will be published in a peer-review journal.